2019
DOI: 10.1242/jeb.204149
|View full text |Cite
|
Sign up to set email alerts
|

Molecular physiology of chemical defenses in a poison frog

Abstract: Poison frogs sequester small molecule lipophilic alkaloids from their diet of leaf litter arthropods for use as chemical defenses against predation. Although the dietary acquisition of chemical defenses in poison frogs is well documented, the physiological mechanisms of alkaloid sequestration has not been investigated. Here, we used RNA sequencing and proteomics to determine how alkaloids impact mRNA or protein abundance in the little devil frog (Oophaga sylvatica), and compared wild-caught chemically defended… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 61 publications
7
45
0
Order By: Relevance
“…The amphibian protein saxiphilin, which binds the lethal marine alkaloid saxitoxin (Mahar et al, 1991;Yen et al, 2019), increased in abundance in the intestines and skin of toxic frogs (Figure 2A, Table 1). We have previously shown that saxiphilin is more abundant in the plasma of non-toxic frogs and that saxiphilin may bind DHQ using thermal shift assays (Caty et al, 2019). These data support the hypothesis that saxiphilin may carry alkaloid toxins in poison frogs.…”
Section: Decahydroquinoline Exposure Induces Proteome Shifts Across Tsupporting
confidence: 78%
See 4 more Smart Citations
“…The amphibian protein saxiphilin, which binds the lethal marine alkaloid saxitoxin (Mahar et al, 1991;Yen et al, 2019), increased in abundance in the intestines and skin of toxic frogs (Figure 2A, Table 1). We have previously shown that saxiphilin is more abundant in the plasma of non-toxic frogs and that saxiphilin may bind DHQ using thermal shift assays (Caty et al, 2019). These data support the hypothesis that saxiphilin may carry alkaloid toxins in poison frogs.…”
Section: Decahydroquinoline Exposure Induces Proteome Shifts Across Tsupporting
confidence: 78%
“…The three experimental groups received fruit flies dusted with a 1% decahydroquinoline (DHQ; Sigma-Aldrich, St. Louis, MO, USA) in a vitamin mix (Dendrocare vitamin/mineral powder, Black Jungle, Turners Falls, MA, USA) for either 1, 4, or 18 days ( Figure 1A). DHQ-like alkaloids are sequestered by O. sylvatica in the wild (Caty et al, 2019) and represent an ecologically relevant treatment. Control frogs (N=3) received flies dusted with vitamin mix without DHQ.…”
Section: Decahydroquinoline Feeding Experimentsmentioning
confidence: 99%
See 3 more Smart Citations